ICT Integrated Pedagogy in a Multicultural Classroom: Experiences of Mathematics Teacher (Interdisciplinary Research in Education, 2019)
Multiculturalism in the present context is a global issue in education. It has not yet been materialized into the education system in Nepal. The education system of a country should prepare students to function in today’s multicultural society. In this regards, this paper focuses on the issues of the management of multicultural classes, and the role of ICT-integrated pedagogy to manage such a classroom context. It also discusses the context, and experiences of teachers that can bring the multicultural classroom situation into the right track. For this purpose, I apply narrative inquiry of two mathematics teachers (one male and one female) of University Campus Kirtipur with more than seven-year experience. In-depth interview, related to their experiences and practices in multicultural mathematics classes, was conducted and found that they face problems to teach students in a multicultural classes such as language problem, content problem, and level of understanding. There are two types of multiculturalism in our classes they are critical multiculturalism, and Liberal multiculturalism. The management of multiculturalism is a great challenge for teachers. Although teachers are less familiar with the management of multicultural class, they try to manage such types of diversity by supporting their students personally through ICT-integrated pedagogy. The finding of the study shows that ICT-integrated pedagogy is the best strategy to manage multicultural classes by respecting students’ personal feelings.